Intention to buy, interactive marketing, and online purchase decisions - Yusepaldo Pasharibu; Jessica Aprilia Soerijanto; Ferry Jie (Jurnal Ekonomi dan Bisnis, 2020)
The digital era changes marketing activities and consumer behavior, particularly by changing conventional transactions into digitalized ones through online marketplaces. Before consumers make purchase decisions, they usually experience a phase in which they have needs and desires to choose, have, and use certain products. This phase is commonly known as intention to buy. However, intention to buy alone is insufficient in encouraging ones to make purchase decisions, especially in the online shopping environment. In this respect, the trust factor in online transactions that is established by maintaining good relationships with consumers through interactive marketing also likely explains online purchase decisions. Consequently, this study tests the effect of intention to buy on online purchase decisions as moderated by interactive marketing at an online marketplace in Indonesia, namely Sale-Stock. Data are generated from 200 respondents with the purposive sampling technique by distributing the questionnaires in Google Form through social media. Data are then analyzed with the multiple regression technique. The results show that intention to buy and interactive marketing affect online purchase decisions, both individually and simultaneously. Further, interactive marketing does not moderate the relationship between intention to buy and online purchase decisions.